Предмет: Алгебра,
автор: Аноним
Разложи на множители: 1,44t2−(t+p)2.
(........t...........p)(.........t...........p)
(в первой скобке — разность, во второй — сумма).
Ответы
Автор ответа:
8
1,44t² - (t + p)² = (1,2t)² - (t + p)² = (1,2t - t - p)(1,2t + t + p) =
= (0,2t - p)(2,2t + p)
Похожие вопросы
Предмет: Математика,
автор: nikitasavichev2197
Предмет: Математика,
автор: Masharu3332
Предмет: Английский язык,
автор: anvarbeksaburo3349
Предмет: Биология,
автор: lilyazvyagina
Предмет: Математика,
автор: ОЛЬЧИК9989